Knowledge, Attitude and Practice of Primary Care Physicians Toward Adult Vaccination in Abha City (Bangladesh Journal of Medical Science, 2018)
Aim of study: To assess knowledge, attitude and practice of primary care physicians offering primary health care (PHC), toward adult vaccination and their own vaccination coverage as well as to identify reasons for low vaccination coverage.Methodology: A cross-sectional study design, this study included 103 PHC physicians in Abha City. A self-administered questionnaire was designed by the researcher for data collection.Results: About three fourths of PHC physicians (73%) had poor knowledge, while 21% had moderate knowledge and only 6% had good knowledge, while 41% had positive attitude toward adult vaccination, 49% had neutral attitude while 10% had negative attitude. Most PHC physicians (70%) had poor practice regarding adult vaccination, while 20% had moderate practice and 10% had good practice. PHC physicians’ knowledge was significantly better among older and non-Saudi physicians (p